2010
DOI: 10.1021/ie1008663
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Rubber Sealant for Preventing Water Leaks

Abstract: Considerable amounts of water are being lost due to leaks. One of the main reasons for experiencing such large water leaks is the premature failure of rubber sealants in valves. Water leaks commonly originate from the presence of chlorine ions in tap water. Here, we demonstrate that the incorporation of surface-modified and highly crystalline carbon nanotubes allows the rubber sealants to maintain their sealing properties without experiencing any distinctive degradation over a wide range of temperature and env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Other researchers have already added MWCNT to aromatic PA membranes in previous studies 7 30 31 to increase the membrane chlorine resistance and in general, they attributed the protection against degradation to the electronic rich nature of the highly sp 2 -hybridized MWCNT or to sacrificial organic functionalities present on the nanotubes surface. We have previously shown that the addition of MWCNT to a polymer matrix reduced the adsorption of chlorine within the matrix, therefore protecting the polymer from the chlorine oxidative degradation 21 . Our XPS semi-quantitative analysis, shown in the supplementary Table SI and supplementary Figs S7c and S7d , confirms that the MWCNT·PA nanocomposite absorbed substantially lower chlorine ions as compared to pure PA-based membranes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers have already added MWCNT to aromatic PA membranes in previous studies 7 30 31 to increase the membrane chlorine resistance and in general, they attributed the protection against degradation to the electronic rich nature of the highly sp 2 -hybridized MWCNT or to sacrificial organic functionalities present on the nanotubes surface. We have previously shown that the addition of MWCNT to a polymer matrix reduced the adsorption of chlorine within the matrix, therefore protecting the polymer from the chlorine oxidative degradation 21 . Our XPS semi-quantitative analysis, shown in the supplementary Table SI and supplementary Figs S7c and S7d , confirms that the MWCNT·PA nanocomposite absorbed substantially lower chlorine ions as compared to pure PA-based membranes.…”
Section: Resultsmentioning
confidence: 99%
“…For these reasons, several studies have been carried out and the degradation mechanism of aromatic PA membranes during chlorine exposure is relatively well-known 19 20 . Recently, our group demonstrated that the addition of MWCNT to rubber can considerably reduce the chlorine-induced degradation of the polymer matrix 21 . Although the degradation mechanism of rubber by chlorine is different from that of PA, particularly due to the lack of hydrolysis, covalent chlorination is a common problem for both polyamide and rubber.…”
mentioning
confidence: 99%
“…This disentanglement relies on a cellulation mechanism, in which MWCNTs and matrix robustly form a three-dimensional nano-continuous structure [45][46][47]. This cellulation technology has generated several composites and has found application in an increasing number of areas [48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…For example, homogeneous dispersions of CNTs are difficult to achieve, and we have difficulty in controlling nanospace properties and adhesion to the matrix material, because extremely long and thin (nanometer size) CNTs form aggregates that intertwine complicatedly with each other [4,5]. However, since 2004, composite materials of aluminum [6][7][8], rubber [9][10][11][12][13][14][15][16], resin [17][18][19], and ceramics [20] have been successively developed; homogeneous dispersions have been achieved and interface phases and 3D structures have been controlled using mixing-and-kneading method, which exploits singular properties of rubber elastic bodies. Rubber seal materials with a thermal resistance of 85 °C, twice improved pressure resistance, and three times greater endurance are now being used for exploration and production in oil fields all around the world [11].…”
Section: Introductionmentioning
confidence: 99%
“…Wetting controls dispersion of the filler into the matrix material, as well as various characteristics of the composite. Also, the diameters of the CNT as filler are presumed to influence the mechanical properties of the nanocomposite [11,16]. In this paper, we report the successful development of high-stiffness rubber materials, and we examine the influence of the composite, which uses natural rubber (NR) as the matrix material and multi-walled carbon nanotubes (MWCNTs) as the filler, on surface properties of MWCNTs.…”
Section: Introductionmentioning
confidence: 99%